Effectiveness of Criminal Sanctions Enforcement against Environmental Pollution by Industrial Corporations in Indonesia: Efektivitas Penegakan Sanksi Pidana atas Pencemaran Lingkungan oleh Korporasi Industri di Indonesia - Lala, Andi; Kosim, Kosim (Medpro, 2025)
Environmental pollution by industrial companies in Indonesia remains a serious issue, threatening environmental sustainability and public safety. Although Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) provides a strong legal basis, its enforcement often lacks effectiveness. This research aims to analyze the forms of environmental criminal offenses committed by industrial companies and the effectiveness of criminal law enforcement carried out by law enforcement agencies. This study employs a normative legal research method with a qualitative-descriptive approach, analyzing relevant regulations, court decisions, and law enforcement practices. Data were gathered through intensive literature review. The findings indicate that the UUPPLH extensively regulates various forms of industrial pollution offenses, from exceeding quality standards to illegal hazardous waste management, which are subject to substantial fines and administrative sanctions. However, law enforcement faces significant challenges, including the complexity of proving corporate fault, limited resources and coordination among law enforcement agencies, and the potential influence of external factors such as the economic power of corporations. Criminal sanctions, particularly fines, have not consistently provided an optimal deterrent effect, and the obligation for environmental restoration post-judgment is often not fully implemented. This study emphasizes the urgency of enhancing the capacity and coordination of law enforcement, as well as the importance of public participation and transparency in legal processes. The contribution of this article lies in its integrative analysis of legal norms and practical enforcement challenges, offering concrete policy recommendations for strengthening the environmental criminal justice system. A limitation of this study is its primary focus on normative aspects, without extensive empirical fieldwork.